His and Hers: Gender, Consumption, and Technology - Horowitz, Roger; Mohun, Arwen (University of Virginia Press, 1998)
The pathbreaking essays in this collection explore the history of consumption by synthesizing discrete historical literatures on consumer culture, gender, and the history of technology. Luxury hotels and the chocolate industry are among the diverse array of topics these authors use to demonstrate that consumption is both a material and a cultural process. Production and consumption become equally inextricable under close analysis. Tools from both the history of technology and gender studies illuminate how these categories intersect. Although broad social and technological trends influence the outcome of these stories, the authors emphasize the agaency of particular groups, including consumers, workers, manufacturers, and the "mediators" who communicate between producers and consumers. This volume will be of interest to historians in a wide range of fields.
Keywords: Business History and gender